The Role of Local Elite in Public Service Innovation in Sleman Regency (Comparative Study of Wukirsari Village and Blue Lagoon Tourism Village) - Nugroho, Hanantyo Sri (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This article intends to provide an overview of the role of local elites in public service innovation. Through a qualitative descriptive approach, this research discusses the dilemmas and success factors of the role of local elites in public service innovation. The objective of this research is the role of Rosyid Ma'ruf and Suhadi as initiators in innovating public services. This problem is interesting to study because there is a role played, where formal actors are able to manipulate community participation due to the formal carrying capacity of the environment while non-formal actors are only limited to practical awareness of the problems that arise at the time and also follow what the actors want. The results showed that public service innovation can be influenced by critical awareness as well as practical awareness of the role of local elites. The tendency of critical awareness arises from the consequences of the actor's understanding of the authority, problems, and existing solutions. That is, actors have the ability to mobilize and direct solutions that are comprehensive. Furthermore, the tendency of practical awareness arises from the consequences of the actor's understanding of the existing problem and solution. That is, the actor has the ability to move and direct the solution that is moving to the solution desired by the actor. The recommendation of this research is the importance of the ability of local elites to understand authority, problems, and solutions so that they can understand how the solution is done to achieve goals that are comprehensive, not only in accordance with what is desired by the elite.